SNARE Complexity in Arbuscular Mycorrhizal Symbiosis - Huisman, Rik; Hontelez, Jan; Bisseling, Ton; Limpens, Erik (Frontiers in Plant Science, 2020)
How cells control the proper delivery of vesicles and their associated cargo to specific plasma membrane domains upon internal or external cues is a major question in plant cell biology. A widely held hypothesis is that expansion of plant exocytotic machinery components, such as SNARE proteins, has led to a diversification of exocytotic membrane trafficking pathways to function in specific biological processes. A key biological process that involves the creation of a specialized plasma membrane domain is the formation of a host-microbe interface (the peri-arbuscular membrane; PAM) in the symbiosis with arbuscular mycorrhizal fungi. We have previously shown that the ability to intracellularly host AM fungi correlates with the evolutionary expansion of both v- (VAMP721d/e) and t-SNARE (SYP132α) proteins, that are essential for arbuscule formation in Medicago truncatula. Here we studied to what extent the symbiotic SNAREs are different from their non-symbiotic family members and whether symbiotic SNAREs define a distinct symbiotic membrane trafficking pathway. We show that all tested SYP1 family proteins, and most of the non-symbiotic VAMP72 members, are able to complement the defect in arbuscule formation upon knock-down/-out of their symbiotic counterparts when expressed at sufficient levels. This functional redundancy is in line with the ability of all tested v- and t-SNARE combinations to form SNARE complexes. Interestingly, the symbiotic t-SNARE SYP132α appeared to occur less in complex with v-SNAREs compared to the non-symbiotic syntaxins in arbuscule-containing cells. This correlated with a preferential localization of SYP132α to functional branches of partially collapsing arbuscules, while non-symbiotic syntaxins accumulate at the degrading parts. Overexpression of VAMP721e caused a shift in SYP132α localization towards the degrading parts, suggesting an influence on its endocytic turn-over. These data indicate that the symbiotic SNAREs do not selectively interact to define a symbiotic vesicle trafficking pathway, but that symbiotic SNARE complexes are more rapidly disassembled resulting in a preferential localization of SYP132α at functional arbuscule branches.